1999
DOI: 10.1111/j.1745-4530.1999.tb00496.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Moisture Sorption in Winged Bean Seed and Gari

Abstract: Experimental data on sorption isotherms of gari and winged bean seeds were used to determine their thermodynamic functions (heat of vaporization, spreading pressure, net integral enthalpy and entropy). The heat of vaporization of both products reduced with increase in moisture content and approached that of saturated water at moisture contents of about 15%. Within the moisture content range of 2.0 and 18.0%, the net integral enthalpy and net integral entropy of gari were respectively higher and lower than thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
74
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 18 publications
(7 reference statements)
11
74
0
2
Order By: Relevance
“…The results shown that the spreading pressure increased with increasing water activity and, at a given water activity, decreased with increasing temperature. The trends of spreading pressures with respect to temperature and water activity for adsorption and desorption were similar to those determined by Fasina et al (1999) for winged bean and gari, Aviara and Ajibola (2002) for melon seed and cassava, McMinn and Magee (2003) for potato.…”
Section: Spreading Pressuresupporting
confidence: 75%
“…The results shown that the spreading pressure increased with increasing water activity and, at a given water activity, decreased with increasing temperature. The trends of spreading pressures with respect to temperature and water activity for adsorption and desorption were similar to those determined by Fasina et al (1999) for winged bean and gari, Aviara and Ajibola (2002) for melon seed and cassava, McMinn and Magee (2003) for potato.…”
Section: Spreading Pressuresupporting
confidence: 75%
“…The design of more efficient drying systems and storage systems for crops require knowledge of energy requirements, state and mode of moisture sorption within them [6]. This could be achieved by stating the correct mathematical models to estimate the heat and mass transfer mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…It is the total energy required to transfer water molecules from vapor state to a solid surface and vice-versa, as well as a measure of work done by a system to accomplish adsorption or desorption process. It is therefore used as an indicator of the state of adsorbed water by solid particles [6]. Isosteric heat is useful in predicting drying models, calculating energy consumption during the drying or wetting of agricultural materials, the design of drying equipment and describing any heat and mass transfer related processes [6,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…It represents the surface excess free energy [24]. It acts as a second pressure [12] and results in increase in surface tension on bare sorption sites due to the sorbed molecules on them [25]. It was calculated using an analytical procedure .…”
Section: Net Isosteric Heat Of Sorptionmentioning
confidence: 99%